How Significant is Instagram in Shaping Personal Branding? Literature Review - Agung Setyawan; Pawito; Andrik Purwasito (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study reviews existing literature on the role of Instagram in shaping personal branding, employing a qualitative method with a literature review approach. With the increasing use of social media, particularly Instagram, by individuals from various professional backgrounds, it is essential to understand the extent to which this platform influences personal branding strategies. Through comprehensive literature analysis, this research identifies the key factors that make Instagram an effective tool for personal branding, as well as the challenges and opportunities users face. These findings provide insights for academics and practitioners on optimizing Instagram for personal branding. The study concludes that Instagram plays a crucial role in shaping personal branding, contingent on strategic and appropriate use. Recommendations for further research and practical implications are provided to maximize the impact of personal branding on Instagram through data-driven approaches and creative strategies